Molecular dynamics simulation of membrane in room temperature ionic liquids - Theng, S.G. (Penerbit Akademia Baru, 2018)
The polyvinylidene difluoride (PVDF) membrane has been a popular material in membrane separation process. In this work, molecular dynamic simulation was done on the PVDF membrane with 100 wt IL and 50 wt IL in GROningen MAchine for Chemical Simulations (GROMACS). The results was evaluated based on potential energy, root mean square deviation (RMSD) and radial distribution function (RDF). The stability and interaction of PVDF were evaluated. Results reveal that PVDF has a stronger interaction to C2bim+ cation compared to water and bromine anion. Both potential energy and RMSD were lower when the weight percentage of IL is higher. This indicates that the IL is able to stabilize the PVDF structure. RMSD reveals that C2bim+ cation is dominant at short distance (less than 1 nm), indicating that strong interaction of cation to PVDF. This understanding of the behavior of PVDF-IL could be used as a reference for future development of stronger membrane. Â© 2018 Penerbit Akademia Baru - All rights reserved.